Googling concussion care in the USA: a critical appraisal of online concussion healthcare providers - Michael J Ellis; Lesley Ritchie; Erin Selci; Stephanie Grossi; Samantha Frost; Patrick J McDonald; Kelly Russell (Concussion)
Aim: To examine the online personnel and practice profiles of concussion healthcare providers in the USA. Methods: We conducted independent, blinded, Google Internet searches for concussion healthcare providers using the terms ‘concussion clinic’ and ‘concussion program’ and each American state and completed a critical appraisal of healthcare personnel and services at these websites. Results: A total of 184 concussion healthcare providers were identified. Despite offering care to traumatic brain injury (TBI) patients, access to professionals with expertise in TBI including neuropsychologists (40.8%), neurologists (33.7%) and neurosurgeons (21.7%) was variable across sites. Conclusion: Concussion healthcare in the USA is presently delivered by a range of healthcare professionals with varying levels of training in TBI offering a variety of services.